Polysémie du verbe « aimer » dans Le roi Lear de W. Shakespeare - Geneviève Lheureux (Lexis: Journal in English Lexicology)
In William Shakespeare’s King Lear, the plot is based on a semantic mistake, which results from the polysemy of the verb love, attested until 1530. Terence Hawkes has shown how the tendency – embodied by the king – to try to gauge precisely, or even put a price on the feelings of those who are dear to us, became lexicalized in English. The tragedy stages the consequences of Lear’s failed attempt at rewarding his daughters measure for measure and exposes the rules of retribution, or poetic justice, as both conventional and illusory.